(untitled) (Eurasian Journal of Philology Science and Education, 2022)
In modern Kazakh literary studies, one of the most pressing problems is to identify the origins, assess the stages of development, formation of national literature and study the features of periodization, as well as to delve into the history of Kazakh literature. In the course of modern research, the national literature is replenished with spiritual and literary monuments that were forgotten after the influence of the policy of «vulgar socialism». Modern Kazakh literary studies change the methodological principles and rely on the leading positions of the world’s literary studies. New trends in this direction require a comprehensive understanding. In this regard, the article is devoted to the problems of the history of the study of Kazakh literature. The paper reviews new directions in the observed sphere of scientific knowledge. Peculiarities of new research, various scientific platforms have been taken into consideration. Special attention was paid to the comparison of works on the history of the study of Kazakh literature, the assessment of the contribution of researchers and their role in the formation and development of scientific directions. At the same time, the movements of scientific thought were considered in retrospect: from early works to modern works. By analyzing specific scientific works, the contribution of modern studies of the history of Kazakh literature is considered. Attention is paid to the presence of a special system in them, the presence of alternative views on solving problems. On the basis of the con-ducted analytical work, new directions of studying the history of Kazakh literature were identified. As the results of the study, new ways of studying the national heritage are presented. The necessity of revising the approaches to the study of literary heritage, taking into account the requirements of modern scientific trends in this field of scientific knowledge, is confirmed.